Modernizing Education: Empowering the Potential of E-Comic Media for Improved Learning Interest and Learning Outcomes - Bukian, I Gusti Ayu Made Winda Pradnyasari; Gading, I Ketut; Bayu, Gede Wira (Universitas Pendidikan Ganesha, 2024)
Low student interest in learning has impact on low learning outcomes due to the lack of use of electronic learning media. This study aims to develop e-comic media that passes acceptability test and effective to increase learning interest and learning outcomes of science and social studies in fifth grade elementary school. This research develops e-comic learning media on the topic of Indonesiaku Kaya Hayatinya using the ADDIE model. The population in this study were eight schools. Sample selection using random sampling technique so as to obtain one control group and one experimental group. The subjects of this study are students from the sample schools. Research data in the form of science and social sciences learning outcomes were obtained through tests in the form of assignments and the acceptability of e-comic media and student interest in learning were obtained through questionnaires. The results of the e-comic media development acceptance test were declared feasible based on reviews by learning material experts, learning media experts, and two expert learning practitioners. The student response test obtained an average product of 4,8 with very good practicality qualifications. The results of the effectiveness test of e-comic media development to increase learning interest and learning outcomes are significant differences between groups of students who use e-comic media and groups of students who do not use e-comic media. This study has implications for e-comics that able to increase students' interest in reading with attractive graphic elements, enrich experience through the presentation of visual information, and help understanding concepts.